PEMIKIRAN TAFSIR SAYYID QUTHUB DALAM FI DZILAL AL-QUR'AN - Supriadi Supriadi (STAI Asy-Syukriyyah, 2015)
Sayyid Qutb, a famous Islamic thinker with traditional conservative variants. Sayyid Qutb became interested in Al-Qu'an from an early age, then spanning a period of intellectual over a period of two different political regimes, which have ties with the colonial West. Sayyid Qutub offers a new method to understand the Qur'an, there are at least two things that the footing. First, the understanding of the Qur'an is done through a reference history and the companions of the prophet, Second, he uses intuition to understand the text. The work done by Sayyid Qutb in interpreting the Qur'an is closely related to the situation that developed in his time, as at that time the Muslims face the challenge of the West, either in the form of philosophy or ideology that developed, so as to respond to the influence of them, Sayyid Qutb tried to make Islam as an ideology. This is the one affecting the interpretation methods, especially in interpreting lafadz at-taghouts.